Modeling of Cutting Mechanics Analysis of Diamond Core Bits - Yao, Jianlin; Liu, Bin; Yao, Kuipeng (International Journal of Natural Resources and Environmental Studies, 2024)
Diamond core bits are essential tools for coring operations in deep formations during oil and gas drilling projects. By establishing a cutting mechanics calculation model for diamond core bits, this study investigates the changes in bit load and torque under the influence of key factors such as bit cutting structure, rock strength, and diamond distribution density. This research is significant for optimizing bit structure, enhancing coring drilling efficiency, and prolonging bit lifespan. This paper conducts modeling analysis of the cutting element loads for various shaped diamond particles, including rectangular, triangular, cylindrical, and spherical shapes. Based on this, a cutting mechanics calculation model for axial and tangential forces of granular spherical diamonds is established using the fundamental principles of elastoplastic mechanics. Consequently, a set of methods for calculating and analyzing the working loads of diamond core bits is developed. The findings of this paper provide a theoretical basis for studying the rock-breaking mechanism of diamond core bits, evaluating drilling efficiency, and optimizing tooth arrangement structures.